Answer:
x = 5 or x = -2 or 3 - 2 x (derivative)
Explanation:
Solve for x over the real numbers:
-x^2 + 3 x + 10 = 0
Multiply both sides by -1:
x^2 - 3 x - 10 = 0
x = (3 ± sqrt((-3)^2 - 4 (-10)))/2 = (3 ± sqrt(9 + 40))/2 = (3 ± sqrt(49))/2:
x = (3 + sqrt(49))/2 or x = (3 - sqrt(49))/2
sqrt(49) = sqrt(7^2) = 7:
x = (3 + 7)/2 or x = (3 - 7)/2
(3 + 7)/2 = 10/2 = 5:
x = 5 or x = (3 - 7)/2
(3 - 7)/2 = -4/2 = -2:
Answer: x = 5 or x = -2
____________________________________
Find the derivative of the following via implicit differentiation:
d/dx(H(x)) = d/dx(10 + 3 x - x^2)
Using the chain rule, d/dx(H(x)) = ( dH(u))/( du) ( du)/( dx), where u = x and d/( du)(H(u)) = H'(u):
(d/dx(x)) H'(x) = d/dx(10 + 3 x - x^2)
The derivative of x is 1:
1 H'(x) = d/dx(10 + 3 x - x^2)
Differentiate the sum term by term and factor out constants:
H'(x) = d/dx(10) + 3 (d/dx(x)) - d/dx(x^2)
The derivative of 10 is zero:
H'(x) = 3 (d/dx(x)) - d/dx(x^2) + 0
Simplify the expression:
H'(x) = 3 (d/dx(x)) - d/dx(x^2)
The derivative of x is 1:
H'(x) = -(d/dx(x^2)) + 1 3
Use the power rule, d/dx(x^n) = n x^(n - 1), where n = 2.
d/dx(x^2) = 2 x:
H'(x) = 3 - 2 x
Simplify the expression:
Answer: = 3 - 2 x